Pengaruh Perkembangan Pariwisata Situ Gunung Terhadap Perekonomian Masyarakat Kadudampit - Alifa Fauziyyah Juhara; Gilang Pratama Putra; Irena Novarlia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tourism development should not only be aimed at providing benefits for tourism managers and tourists, but also must have a positive impact on the people who live around it. Therefore, tourism managers need to consider economic sustainability for the surrounding community as well. This study aims to analyze the relationship between the influence of Situ Gunung tourism development on the economy of the Kadudampit Community. The method used in this research is quantitative method with linear regression analysis technique. The population in this study is the Situ Gunung tourism manager and the Kadudampit community. The results of the analysis show that the Situ Gunung Tourism Development variable (X) has an effect and is significant to the Situ Gunung Community Economy (Y), with a large influence of 51.6%.